Experience in the treatment of type C congenital esophageal atresia using a staged approach - Yong Zhao; Shihui Tan; An Wang; Shuangshuang Li; Junmin Liao; Dingding Wang; Kaiyun Hua; Yichao Gu; Yanan Zhang; Jinshi Huang (BMC Surgery)
Abstract Background In select patients with type C esophageal atresia, primary anastomosis is not appropriate and a staged approach is required. We aim to summarize our experience in the management of type C EA using a staged approach. Methods A retrospective chart-review of patients with type C EA admitted to Beijing Children’s Hospital between July 2020 to October 2023 were conducted. Those diagnosed with type C EA who were not amendable to primary anastomosis were included for analysis. Clinical information was recorded, and follow- up was performed. Results Seven (five boys) patients with type C EA who received staged repair were included in the study. Initial surgeries included thoracotomy and thoracoscopy. 71% (5/7) patient had complications after the initial surgery, including pyopneumothorax, pneumonia, recurrent tracheoesophageal fistula (rTEF), and anastomotic leak. Esophageal elongation techniques were applied in 3 patients. All delayed anastomosis were performed thoracoscopically, except for in one case where spontaneous fistulization occurred and no anastomosis were necessary. Complications after delayed anastomosis included recurrent esophageal pulmonary fistula (rEPF) in 50% (3/6), anastomotic leak in 33% (2/6), and esophageal stricture in all (6/6) patients. After a median follow-up of 14 months (range: 2–24), all patients were in generally good condition. Conclusion Primary operations should be kept simple and minimal in patients diagnosed with type C EA who are not appropriate for primary anastomosis. Internal traction is an effective method that allows for subsequent anastomosis. Intraoperative indocyanine green fluorescence can aid in fistula determination and anastomosis.